Is Living in African Cities Expensive? - Nakamura, Shohei; Harati, Rawaa; Lall, Somik V.; Dikhanov, Yuri M.; Hamadeh, Nada; Vigil Oliver, William; Rissanen, Marko Olavi; Yamanaka, Mizuki (World Bank, Washington, DC, 2016)
Although several studies have examined why overall price levels are higher in richer countries, little is known about whether there is a similar relationship at the urban and city level across countries. This paper compares the price levels of cities in Sub-Saharan Africa with those of other regions by analyzing price information collected for the 2011 round of the International Comparison Program. Readjusting the calculated price levels from national to urban levels, the analysis indicates that African cities are relatively more expensive, despite having lower income levels. The price levels of goods and services consumed by households are up to 31percent higher in Sub-Saharan Africa than in other low- and middle-income countries, relative to their income levels. Food and non-alcoholic beverages are especially expensive, with price levels around 35 percent higher than in other countries. The paper also analyzes price information collected by the Economist Intelligence Unit's Worldwide Cost of Living Survey, and obtains a similar result, indicating higher prices of goods and services in African cities.